What the fireflies knew : a novel - Harris, Kai (Tiny Reparations Books, 2022)
"A coming-of-age novel told from the perspective of an eleven-year-old over the course of a single summer, as she tries to make sense of her new life with her estranged grandfather and sister after the death of her father and disappearance of her mother"--